Pengaruh Value Clarification Technique terhadap Hasil Belajar PKn Siswa Kelas IV di SD Negeri Cengkareng Barat 03 Pagi - Fauzan, Muhammad Iqbal; Saputri, Rahmawati Eka; Puspita, Dayu Retno (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The purpose of this study is to determine whether students who use the Value Clarification Technique model and students who do not use the model vary in their learning results for civics. This study employed a non-equivalent control group design and a quasi-experimental design method. Class IV students at SD Negeri Cengkareng Barat 03 Pagi made up the population of this study. A sample of 56 students were divided into two groups, class IV A and class IV B, with class IV A serving as the control class and class B as the experimental class. Techniques for gathering data that use test questions as the primary data source and focus on learning outcomes. The findings of hypothesis testing using the t test in the control class and experimental class at the conclusion of learning (posttest) yielded tcount = 2.935 with a significance level of 5% (=0.05) and ttable = 2.005, respectively. H0 is rejected because 2.935 > 2.005 (tcount > ttable). According to the findings of the research, adopting the Value Clarification Technique model has an impact on students' learning outcomes in class IV civics courses.